Glucosamine-anchored doxorubicin-loaded targeted nano-niosomes: pharmacokinetic, toxicity and pharmacodynamic evaluation. (13th September 2016) - Pawar, Smita; Shevalkar, Ganesh; Vavia, Pradeep
Abstract: Background: Efficacy of anticancer drug is limited due to non-selectivity and toxicities allied with the drug; therefore the heart of the present work is to formulate drug delivery systems targeted selectively towards cancer cells with minimal toxicity to normal cells. Purpose: Targeted drug delivery system of doxorubicin (DOX)-loaded niosomes using synthesized N-lauryl glucosamine (NLG) as a targeting ligand. Methods: NLG-anchored DOX niosomes were developed using ethanol injection method. Results: Developed niosomes had particle size <150 nm and high entrapment efficiency ∼90%. In vivo pharmacokinetics exhibited long circulating nature of targeted niosomes with improved bioavailability, which significantly reduced CL and Vd than DOX solution and non-targeted niosomes (35 fold and 2.5 fold, respectively). Tissue-distribution study and enzymatic assays revealed higher concentration of DOX solution in heart while no toxicity to major organs with developed targeted niosomes was observed. Solid skin melanoma tumor model in mice manifested the commendable targeting potential of targeted niosomes with significant reduction in tumor volume and high % survival rate without drop in body weight in comparison with DOX solution and non-targeted niosomes of DOX. Conclusion: The glucosamine-anchored DOX-loaded targeted niosomes showed its potential in cancer targeted drug therapy with reduced toxicity. Abbreviations: ALT alanine transaminase CL clearance CPK creatinine phosphokinase DOX doxorubicin EDC.HCL ethyl carbidimide hydrochloride GLUT glucose transporter GSH glutathione S-transferase LDH lactate dehydrogenase LHRH luteinizing hormone-releasing hormone MDA malonaldehyde NHS N-hydroxy succinimide NLG N-lauryl glucosamine NTAR DoxNio non-targeted doxorubicin niosomes PBS phosphate buffer saline RGD argynyl glycyl aspartic acid SGOT serum glutamate oxaloacetate transaminase SGPT serum glutamate pyruvate transaminase SOD superoxide dismutase TAR DoxNio targeted doxorubicin niosomes Vd volume of distribution